2010
DOI: 10.3168/jds.2010-3143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioethanol plant and coproduct type on the metabolic characteristics of the proteins in dairy cattle

Abstract: The dramatic increase in bioethanol production in Canada has resulted in millions of tonnes of different types of coproducts: wheat dried distillers grains with solubles (DDGS), corn DDGS, and blend DDGS (e.g., wheat:corn 70:30). The objectives of this study were 1) to investigate the effect of DDGS type and bioethanol plant on the metabolic characteristics of the proteins and the total truly digested and absorbed protein supply to dairy cattle using the DVE/OEB system and 2) to compare the metabolic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 21 publications
6
45
1
1
Order By: Relevance
“…The general high rumen bypass value for DDGS as compared with that of the grain is explained by the reduction of the protein amide I to amide II ratio during fermentation and drying (Li et al, 2012). Our RBP-values for maize and wheat DDGS are similar to those of Nuez-Ortín and Yu (2010), who obtained on average 66.1% and 54.4%, In our study intestinal digestibility of RBP was determined by incubating small nylon bags with residual material after 12 h of rumen incubation in the duodenum and collection of the bags in the faeces. This is considered as the reference method for determining dRBP in the Dutch protein system (Van Duinkerken et al, 2011).…”
Section: Rumen Degradation Of Nutrients Protein Value and Aassupporting
confidence: 60%
See 2 more Smart Citations
“…The general high rumen bypass value for DDGS as compared with that of the grain is explained by the reduction of the protein amide I to amide II ratio during fermentation and drying (Li et al, 2012). Our RBP-values for maize and wheat DDGS are similar to those of Nuez-Ortín and Yu (2010), who obtained on average 66.1% and 54.4%, In our study intestinal digestibility of RBP was determined by incubating small nylon bags with residual material after 12 h of rumen incubation in the duodenum and collection of the bags in the faeces. This is considered as the reference method for determining dRBP in the Dutch protein system (Van Duinkerken et al, 2011).…”
Section: Rumen Degradation Of Nutrients Protein Value and Aassupporting
confidence: 60%
“…This is considered as the reference method for determining dRBP in the Dutch protein system (Van Duinkerken et al, 2011). No other recent studies with DDGS were found where this in situ technique was used and mostly a three-step in vitro procedure with pepsin and pancreatin was applied (Mjoun et al, 2010;Nuez-Ortín and Yu, 2010;Li et al, 2012). Nuez-Ortín and Yu (2010), who obtained similar RBP-values as in our study, estimated a mean dRBP of 81.3%, 82.5% and 93.9% for wheat, maize and blend DDGS, respectively, thus some 10% lower than our values for WDDGS and MDDGS, but surprisingly a similar value for BDDGS.…”
Section: Rumen Degradation Of Nutrients Protein Value and Aasmentioning
confidence: 99%
See 1 more Smart Citation
“…DDGS are a key by-product from ethanol industry, and extensively used in animal feed industry. The nutritive value of dried distillers grain solubles (DDGS) from wheat after ethanol production, makes them an excellent source of protein and energy for dairy and beef cattle [17][18][19]. Subsequent to the process of bioethanol production, ethanol fermentation utilizes most of the starch from grain kernels hence concentrates the remaining components, mainly protein, fiber, fat and minerals into DDGS [37].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to the process of bioethanol production, ethanol fermentation utilizes most of the starch from grain kernels hence concentrates the remaining components, mainly protein, fiber, fat and minerals into DDGS [37]. Wheat DDGS provides many compounds which could be categorized as digestible and available nutrients to animals [17][18][19]. DDGS from wheat contains higher amounts of dry matter (DM, 938 g/kg), crude protein (CP, 393 g/kg) and starch (63 g/kg) [17].…”
Section: Introductionmentioning
confidence: 99%